River Dynamics and Integrated River Management - Wang, Zhao-Yin; Lee, Joseph H.W; Melching, Charles S. (Springer Berlin Heidelberg : Imprint: Springer, 2015)
"River Dynamics and Integrated River Management" provides comprehensive information on rivers for integrated management, including natural processes, stresses resulting from human activities, and restoration of various parts of the river basin, including the watershed, mountain streams, alluvial rivers, estuaries, and natural and man-made lakes. Essential concepts, traditional and modern, such as river patterns, step-pool systems, vegetation-erosion charts, habitat diversity, and flushing times of bays, are clearly defined physically and explained with figures and pictures. Detailed mathematics and rigorous analyses are avoided so as to facilitate a holistic view of the subject of integrated river management. Researchers can easily familiarize themselves with the science of river management in its widest sense with the impressive pictures and examples in this book. Dr. Zhaoyin Wang is a professor at the Department of Hydraulic Engineering, Tsinghua University, China. Dr. Joseph H.W. Lee is a Chair Professor at the Department of Civil and Environmental Engineering, The Hong Kong University of Science & Technology, China. Dr. Charles S. Melching is a Professor at the College of Engineering, Marquette University, Milwaukee, WI, USA.